Synthesis of 2-azabicyclo[m.n.0]-alkanes and their application towards the synthesis of strychnos and stemona classes of alkaloids - Majumder, Binoy; Pandey, Ganesh (European Journal of Organic Chemistry, 2020)
2-Azabicyclo[m.n.0]alkane ring systems, the conceptual precursors towards the synthesis of Strychnos and Stemona classes of alkaloids, were synthesized from tert-butyl 2-(phenylsulfonyl)-7-aza-bicyclo[2.2.1]hept-2-ene-7-carboxylate by alkyl Grignard reaction and intramolecular cyclisation of the in situ generated ring opening product 2. The synthesized cis-hexahydroindole 3 and cis-octahydro-benzo[b]azepine 5 scaffolds were utilized to construct the advanced intermediates 25 and 35, respectively, towards the synthesis of the corresponding Strychnos and Stemona classes of alkaloids.
Keywords: alkaloids; amines; Grignard reaction; Michael addition; Natural products